Becoming a pharmacist: the role of curriculum in professional identity formation - Noble C; Coombes I; Shaw PN; Nissen LM; Clavarino A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: To understand how the formal curriculum experience of an Australian undergraduate pharmacy program supports students' professional identity formation. Methods: A qualitative ethnographic study was conducted over four weeks using participant observation and examined the 'typical' student experience from the perspective of a pharmacist. A one-week period of observation was undertaken with each of the four year groups (that is, for years one to four) comprising the undergraduate curriculum. Data were collected through observation of the formal curriculum experience using field notes, a reflective journal and informal interviews with 38 pharmacy students. Data were analyzed thematically using an a priori analytical framework. Results: Our findings showed that the observed curriculum was a conventional curricular experience which focused on the provision of technical knowledge and provided some opportunities for practical engagement. There were some opportunities for students to imagine themselves as pharmacists, for example, when the lecture content related to practice or teaching staff described their approach to practice problems. However, there were limited opportunities for students to observe pharmacist role models, experiment with being a pharmacist or evaluate their professional identities. While curricular learning activities were available for students to develop as pharmacists e.g. patient counseling, there was no contact with patients and pharmacist academic staff tended to role model as educators with little evidence of their pharmacist selves. Conclusion: These findings suggest that the current conventional approach to the curriculum design may not be fully enabling learning experiences which support students in successfully negotiating their professional identities. Instead it appeared to reinforce their identities as students with a naïve understanding of professional practice, making their future transition to professional practice challenging.